The effect of working capital management approaches on sme business performance in the northern province of sri lanka - Sooriyakumaran, L.; Thrikawala, S.S.; Pathirawasam, C. (University of Jaffna, 2022)
Purpose: Small Medium Enterprises (SMEs) play an essential role in the sustainable development of developed or developing countries to achieve inclusive economic growth. The World bank recommended this sector for the fast recovery from 30 years of internal conflict in the Sri Lankan economy. These SMEs face severe challenges due to a lack of knowledge in working capital management approaches. The purpose of this study is to examine the impact of working capital management approaches (WCMA) on the business performance (BP) of SMEs in the context of a developing economy, Sri Lanka. Methodology: This study uses a deductive research approach and quantitative techniques to assess the working capital management approaches and performance of SMEs in Northern Province. To measure WCMA, the study employs cash management, receivable payable management, and inventory and business performance were measured by sales growth, profit growth, and total asset growth. 410 registered SMEs from the population of 24,316 (until 2018) were selected as samples of 33 Divisional Secretary by using the proportionate stratified random sampling method and Slovene's formula. Primary data was collected through a semi-structured questionnaire. Descriptive and inferential analysis methods were done using Excel, SPSS, and SEM AMOS. Findings: The results reveal a significant positive impact of WCMA on BP. The factors of WCMA, cash management (CM), payable receivable management (PRM), and inventory management (IM) show the critical ratio (CR or t-value) is greater than 1.96 for an estimate (regression weight). In other words, the regression weight for CM, PRM, and IM in the prediction of BP is significantly different from zero at the 0.01 level (two-tailed). Its statistics show that the WCMA of the SMEs in the NP has a significant influence on BP. The study reveals the need for SMEs to ensure efficient WCMA to maximize BP. Research limitations: This study has covered the limited measurement of WCMA, the present state of SMEs in the Northern Province which are registered under the DS office. It is better to conduct a survey in the future using data collected from other measurement variables and methods and all other provinces of Sri Lanka. Implications: Most of the sample SMEs determined the cash management and inventory management based on the owner/manager's experience. Experience is viewed as more important than theory in practicing cash management. To strengthen their decision, they should follow the proper working capital approaches of managerial accounting. Furthermore, the improvement in WCMA leads to an improvement in business performance. Hence the owners/managers of SMEs have to increase their managerial accounting strategy to monitor and utilize the working capital approaches, like management of cash, payable, receivable, and inventory to ensure the most financially efficient operation of the business. Accounting skills are necessary for successful entrepreneurial and SME development in Sri Lanka. This is because the inability to install a proper accounting system would prevent business monitoring, reporting, and performance evaluation that are relevant to the business's survival.
Keywords: Working capital management approaches; SMEs; Business performance